Validity and Reliability of the Sleep and Lifestyle Questionnaire - ERGÜN, AYŞE (GALENOS YAYINCILIK, 2019)
Objective: The aim of this study was to investigate the validity and reliability of the Turkish version of the Sleep and Lifestyle Questionnaire for adolescents. Materials and Methods: The Sleep and Lifestyle Questionnaire consists of 12 questions developed to assess sleep, television, and computer habits of adolescents. The questionnaire was applied to a total of 1.476 students, and 112 students were retested four weeks later. The content validity of the questionnaire was evaluated by opinions from 10 experts, construct validity was evaluated by chi-square analysis. The test-retest was performed for the reliability of the questions in the questionnaire and kappa for the categorical variable, Spearman's correlation analysis for ordinal data, and the percentage of agreement for continuous variables were calculated. Results: Content validity index of Sleep and Lifestyle Questionnaire was found as 0.99. The chi-square analysis of the construct validity demonstrated that the students whose sleep time was less than the median has a statistically significant higher rate of falling asleep, difficulty in awakening, and being sleepy at school. In the Sleep and Lifestyle Questionnaire

having a television in the bedroom which was categorically variable, test-retest kappa value was 0.84, test-retest correlations of four questions contain ordinal variables were between 0.66-0.81, and the percentage of test-retest agreement of six continuously varying questions was found between 50.9-84.8%. Conclusion: The Sleep and Lifestyle Questionnaire was found to be a valid and reliable tool. The questionnaire can be used to assess lifestyle factors that affect sleep habits and sleep patterns of adolescents in school health studies.
Keywords: Sleep; Sleep and Lifestyle Questionnaire; validity; reliability; COMPUTER HABITS; ADOLESCENTS; DURATION; AGE; CHILDREN; TELEVISION; CHILDHOOD; QUALITY